Negative Political Communication in Online Video Advertisements: Case Study of 2016 Lithuanian Parliamentary Election - Šuminas, Andrius; Aleksandravičius, Arnas; Gudinavičius, Arūnas (Political Preferences, 2017)
In the course of election campaigns politicians and political parties try their best to highlight their most favored topics that would help them draw public attention and increase people’s regard for specific political figures. In contrast to the positive communication content announced during an election campaign, candidates sometimes choose negative messages that focus on their opponents’ weaknesses (real or imagined) rather than the strengths of the candidates announcing those messages. The goal of this research is to identify the forms and means of negative communication used in political video advertisements during Lithuanian parliamentary election of 2016. To achieve our goal, we analyze the political video advertisements that were categorized as negative communication. We categorize and analyze the advertisements by using concepts of forms of negativity and targets of negativity.Our findings suggest that negative communication is being used by Lithuanian political organizations, but positivity is still dominant in political video advertisements. Despite that, negative aspects of communication are used by different parties, in different and diverse forms and targets. Key words: negativity, political communication, online video advertisements, election campaigns